Bio-resources in Palm Oil Mill Effluent (POME) as value added products: a review / Muhamad Ariff Mat Rifin - Mat Rifin, Muhamad Ariff (Faculty of Plantation and Agrotechnology, 2019)
Malaysia was the second larger producer and exporter of palm oil to the worldwide after Indonesia. The increasing producing palm oil by mill resulted in huge amount of waste production such palm oil mill effluent (POME) which cause environmental problem. POME have been treated through end-of-pipe processes and it is worth to considered potential value of POME through cleaner production. Research and development in biotechnology was a great deal in finding methods of managing waste through cleaner production which based on 5R policy reduction, replacement, recovery, reuse and recycling. This review emphasizes on reusing the bio-resources in POME to produce different value added products through biotechnology advances such as fertilizer, energy sources, fermentation media, food for animal and aquatic organism. These high value added products can generate income and contribute in environmental protection. The benefits of these products highly contribute to the sectors of plantation, pharmacy, livestock, electricity and fuel. This is alternative of better POME management to treat the waste by millers instead of producing waste only to cause the environmental impact.